Pengaruh Kerusakan Jack Hydraulic Terhadap Proses Bongkar Muat di MV. Sri Wandari Indah - Muhammad Widiyantoro; Agus Subardi; Ahmad Ndori (Politeknik Ilmu Pelayaran Semarang, 2020)
Sea transportation is seen as the most effective means of responding to the high demand for a commodity. The development of industry 4.0 and society 5.0 has a big influence on the economic growth of a country. Loading and unloading must go well, so efforts are needed to ensure its implementation. Delay in unloading due to hydraulic leakage. The captain and guard officer as more experienced parties are expected to make efforts to prevent it. Coordinating work when unloading shows that the ship has followed procedures and efforts to repair hydraulic leaks. The method used by researchers to analyze problems is the fishbone analysis method. Research data obtained from primary data and secondary data, while data collection was obtained from observations, interviews, descriptive and literature. Fishbone analysis aims as an effort made to change the data from the results of a study into simpler information, so that it is easy to use to draw conclusions. Based on the results of this study, hydraulic maintenance was further improved and procurement of spare parts continued to be pursued by the ship. In addition, the company's management also affects the performance of the crew on the ship so that there is a need for improvement in the company's management of the ship.